Enhancing Chemistry Learning Motivation among Visually Impaired Students through a Smart Interactive Braille Periodic Table - Inka Putri Suryani; Kusumawati Dwiningsih; Siti A'isatul Hijriyah; Rizkyana Nur Aisyah; Nani Fitria Ramadhani; Rohimatus Nur Aulia Putri; Maharani Agustina Arivi (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Abstract chemistry concepts and visual access limitations contribute to low chemistry learning motivation among students with visual impairments. Most chemistry concepts are presented through visual representations, such as chemical symbols and the periodic table, making them difficult for students with visual impairments to access through conventional learning media. This study aims to analyze learning motivation through the implementation of the smart interactive braille periodic table. The study employed a one-group pretest-posttest design using purposive sampling involving six students with visual impairments in Surabaya. Data were collected through a learning motivation questionnaire, student response questionnaire, learning implementation observation sheet, and student activity observation sheet, and were analyzed using inferential statistical and descriptive analyses. The results showed that the average learning motivation score increased from 51.67 on the pre-test to 88.50 on the post-test, with an N-Gain of 0.761 (high). Furthermore, the paired-sample t-test showed a significant difference (p < 0.05) and a very large effect size (Cohen's dz = 4.58). In conclusion, the smart interactive braille periodic table showed potential to enhance chemistry learning motivation among students with visual impairments and provides an adaptive, technology-based approach to multisensory inclusive chemistry learning